Ethnicization and identity construction in Malaysia - Holst, Frederik (London : Routledge, 2012)
'Provide[s] an in-depth and multifaceted study of the processes of ethnicization and identity construction in Malaysia, from the colonial period until the present'--Publisher's description.
Includes bibliographical references (p. [225]-235) and index.
Keywords: Ethnicity -- Malaysia; Malaysians -- Ethnic identity; Malaysia -- Ethnic relations